Pemetaan Kesesuaian Nilai Lahan dengan Zona Nilai Tanah di Kota Padang Panjang - Jannesman, Hafiz; Ahyuni, Ahyuni (Lembaga Yasin AlSys, 2024)
This research aims: (1) To determine the distribution of land values based on the determining parameters of land values in Padang Panjang City. (2) To identify the Zona Nilai Tanah (ZNT) in Padang Panjang City. (3) To analyze the level of conformity between land values and Zona Nilai Tanah (ZNT) spatially in Padang Panjang City. The method used in this research is a weighted quantitative hierarchical method, which is then analyzed using overlay and classified with Equal Interval data classification. The research results show that land values in Padang Panjang City are dominated by the moderate category with an area of 853,28 ha or 36,83%, and in the Zona Nilai Tanah (ZNT), it is dominated by the low category with an area of 1.274,25 ha or 73,65% of the total area. The overlay results between the land value map and the classified Zona Nilai Tanah (ZNT) map produced a conformity level of only 20,32% with an area of 351,57 ha, and the non-conformity category reached 79.68% with an area of 1.378,53 ha.The dominant factor causing the discrepancy is due to the difference in spatial data distribution between land values and Zona Nilai Tanah (ZNT).